2015
DOI: 10.1007/978-3-319-18144-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide and Urogenital Tract

Abstract: In this chapter the role played by H2S in the physiopathology of urogenital tract revising animal and human data available in the current relevant literature is discussed. H2S pathway has been demonstrated to be involved in the mechanism underlying penile erection in human and experimental animal. Both cystathionine-β synthase (CBS) and cystathionine-γ lyase (CSE) are expressed in the human corpus cavernosum and exogenous H2S relaxes isolated human corpus cavernosum strips in an endothelium-independent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…The H 2 S pathway is involved in many physiological and pathological processes in different organs and apparatuses in animal experimental models and in human [ 5 8 ]. Recently, a role for the L-cysteine/H 2 S pathway has been proposed in human urogenital tract [ 9 15 ]. Within this context, we have previously demonstrated that CBS and CSE are both expressed in the human bladder and that either an H 2 S donor or L-cysteine relaxes human bladder strips.…”
Section: Introductionmentioning
confidence: 99%
“…The H 2 S pathway is involved in many physiological and pathological processes in different organs and apparatuses in animal experimental models and in human [ 5 8 ]. Recently, a role for the L-cysteine/H 2 S pathway has been proposed in human urogenital tract [ 9 15 ]. Within this context, we have previously demonstrated that CBS and CSE are both expressed in the human bladder and that either an H 2 S donor or L-cysteine relaxes human bladder strips.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have addressed the role of H 2 S as possible downstream mediator following activation of M receptors within the urothelium. Indeed, endogenous H 2 S is a signaling molecule which participates in the regulation of various physiological processes in human urogenital-tract 11 16 17 21 24 25 26 . The choice of the urothelium stems from the finding that CBS is markedly expressed in the urothelium as compared to CSE and that its activity is specifically enhanced upon phosphorylation 21 .…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S, is the third gaseous transmitter along with nitric oxide (NO) and carbon monoxide, formed by L-cysteine mainly through the action of cysthationine-β-synthase (CBS) and cysthationine-γ-lyase (CSE) 12 13 14 15 . It is endogenously produced in urinary bladder of trout, mouse, and rat implying that the contribution of this pathway to bladder function is conserved in different species including human 16 . Moreover, animal pre-clinical studies showed that H 2 S causes smooth muscle relaxation and/or contraction depending on the species and experimental conditions used 17 18 19 20 .…”
mentioning
confidence: 99%
“…As a member of gasotransmitters, H 2 S has been identified in several tissues of male reproductive system from various mammalian species (Sugiura et al, 2005; d’Emmanuele di Villa Bianca et al, 2009; Li et al, 2011; di Villa Bianca et al, 2015). However, the existence and the functional roles of H 2 S in epididymis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the male reproductive system, endogenous H 2 S-generating enzymes CBS and CSE have been identified in human penile, rat testis, and vas deferens (Sugiura et al, 2005; Li et al, 2012; di Villa Bianca et al, 2015). Similar to rat testis, our results demonstrated the distribution of these two enzymes was distinct in rat epididymal tissue.…”
Section: Discussionmentioning
confidence: 99%